Oxidative Delignification and Bleaching of Alkaline Sulphite-Anthraquinone Wheat Straw Pulp - Yaqoob, Naila; Stack, Karen; J. Cheema, Kausar; Mateen, Bushra; Rehman, Ishtiaq-ur- (Asian Journal of Chemistry, 2011)
In this study, the oxidative delignification and bleaching of alkaline sulphite-anthraquinone (AS/AQ) wheat straw pulp is reported. Oxygen, oxone and hydrogen peroxide were used to achieve targeted brightness > 80 % ISO without compromising the other pulp properties i.e., burst, tensile and tear index, kappa number, CED viscosity, hexenuronic acid, accelerated ageing and percentage yield of bleached pulp. The effect of various reaction parameters such as alkali, pulp consistency, temperature, time and bleaching agent dosage were optimized for each stage of bleaching.